1998
DOI: 10.1093/jat/22.6.503
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Validation Study of Drug Evaluation and Classification Program: Alprazolam, d-Amphetamine, Codeine, and Marijuana

Abstract: The Drug Evaluation and Classification (DEC) program is used by police agencies to identify drivers impaired because of drug use and to determine the class(es) of drug causing the impairment. The primary goal of this study was to determine the validity of the DEC evaluation in predicting whether research volunteers were administered alprazolam, d-amphetamine, codeine, or marijuana. A secondary goal was to determine the accuracy of Drug Recognition Examiners (DREs) in detecting if subjects were dosed with these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…Although not significant, some improvements on the OLS test were observed in the amphetamine conditions. This is consistent with previous research where Heishman et al (1998) found that a decrease in errors on the OLS test was the third best predictor for the presence of dexamphetamine, indicating that the OLS test may not be an appropriate measure of drug presence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although not significant, some improvements on the OLS test were observed in the amphetamine conditions. This is consistent with previous research where Heishman et al (1998) found that a decrease in errors on the OLS test was the third best predictor for the presence of dexamphetamine, indicating that the OLS test may not be an appropriate measure of drug presence.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research that has reported improvements on the OLS test after the administration of dexamphetamine (Heishman et al 1998).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…The suspected drivers in the present study were mostly apprehended due to conspicuous driving or involvement in traffic accidents, indicating poor driving performance. This was reflected in a high percentage of the drivers being judged impaired compared to experimental studies (Heishman et al, 1998;Silber et al, 2005b). Some drivers having taken amphetamines may not have been apprehended due to a lower degree of impairment.…”
Section: Discussionmentioning
confidence: 98%
“…Such doses give rise to a C max about 0.10-0.15 mg/l (Silber et al, 2005a). In most of these studies no relationship between impairment and blood amphetamines concentrations or the doses of amphetamines taken has been found (Angrist et al, 1987;Asghar et al, 2003;Brauer et al, 1996;Evans et al, 1976;Heishman et al, 1998;Perez-Reyes et al, 1992;Pickworth et al, 1997;Silber et al, 2005b;Slattum et al, 1996). In real-life settings doses taken are commonly much higher (50-300 mg or more), and are often taken intravenously in binges.…”
Section: Discussionmentioning
confidence: 99%